2000
DOI: 10.1067/mtc.2000.110189
|View full text |Cite
|
Sign up to set email alerts
|

Histologic and physiologic evaluation of skeletonized internal thoracic artery harvesting with an ultrasonic scalpel

Abstract: The internal thoracic artery skeletonization method with an ultrasonic scalpel (Harmonic Scalpel: output level 2) appears to be a safe and reliable method of skeletonized internal thoracic artery harvesting when branches are sectioned at least 1 mm distal to their origin at a sufficiently slow speed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…These results were found, probably as a result of better sternal perfusion after ITA skeletonization compared to the pedicled ITA [22][23][24][25][26][27][28]. Boodhwani et al [26] conducted a study with 48 patients, in which each individual was submitted to CABG using bilateral ITA, and all ITAs were dissected skeletonized in the left side and pedicled in the right side.…”
Section: Discussionmentioning
confidence: 99%
“…These results were found, probably as a result of better sternal perfusion after ITA skeletonization compared to the pedicled ITA [22][23][24][25][26][27][28]. Boodhwani et al [26] conducted a study with 48 patients, in which each individual was submitted to CABG using bilateral ITA, and all ITAs were dissected skeletonized in the left side and pedicled in the right side.…”
Section: Discussionmentioning
confidence: 99%
“…The histological study confirmed that a different devices such as ultrasonic scalpel or high frequency electrocotery application on the branches more than 1 or 5 mm away from the ITA itself did not cause any endothelial injury [11,12]. Therefore, our investigation was done by carrefully observation during the harvesting with the aid of low voltage electrocotery.…”
Section: Discussionmentioning
confidence: 83%
“…Higami et al [10] presented histological results of tissue submitted to USS, demonstrating its safety when used at a distance of more than 1 mm from the vessel; less than 1 mm may cause slight injuries in adjacent tissues. With coagulation resulting from collagen molecule degradation, the emanated heat is around 50ºC to 60ºC.…”
Section: -Final Aspect Of Skeletonized Internal Thoracic Arterymentioning
confidence: 99%
“…We use level 3 USS power. The intercostal branches are coagulated for 2 to 3 seconds and sectioned as far from the arterial wall as possible (at least 1 mm from the ITA) (Figure 3), so that adjusted protein coagulation of the branches is possible and not to damage the ITA trunk [10]. We adopted the hook-type blade and considered level 3 ideal, because it presented good coagulation with a slower cut.…”
Section: Dissection Of Internal Thoracic Arterymentioning
confidence: 99%
See 1 more Smart Citation